Macroeconometric modeling and the SSRC's Committee on Economic Stability, 1959-1963 - Juan Acosta; Erich Pinzón-Fuchs (Duke University, Center for the History of Political Economy (CHOPE), 2018)
We study the construction of the macroeconometric model of the Committee on Economic Stability (CES) of the Social Science Research Council (SSRC) in the early 1960s using the CES's archival records. Building this model was central not only to set the bases for the subsequent construction of other models such as the Brookings Model (1963-1972) and the FRB-MIT-Penn model (1966-1974) but also to consolidating large-scale macroeconometric modeling as a scientific practice at the frontier of macroeconomics in the 1960s. We provide a detailed account of the complex establishment of the Committee and argue that the organization of the CES was the response of an important group of economists concerned about the instability of the US economy and wanting to develop new methods with the "widest possible degree of acceptance" to understand concrete fluctuations of the economy and to act upon them to maintain stability. As the first model-building enterprise of this size, the project's many challenges in terms of logistics, data, and computing capacity, evidence the importance of configuring a specific institutional and material context necessary to develop this new scientific practice. In this sense, we discuss the functioning and management of this ambitious project and, in particular, the structure and organization of the team in charge of the model (or "federation of research projects"), which was structured around more than 20 researchers based in different locations. We argue that the CES was successful in bringing together academics and people from government agencies and in the very practical purpose of producing, collecting, centralizing, and managing data for the purpose of generating quantitative policy analysis.
Keywords: B22; B23; B4; 330; History of macroeconomics; macroeconometric modeling; Committee on Economic Stability; Social Science Research Council; large-scale macroeconometric models; Brookings Model